Analysis of the effects of electromobility and renewable energy integration on grid power quality - Akintayo Oluwakemi K.; Longe Omowunmi M.; Oni Oluwafemi E. (E3S Web of Conferences)
In this work, the effects of renewable energy and electromobility integration into the power distribution network were analyzed. The energy systems (renewable energy sources and electromobility source systems) were modelled in a MATLAB/SIMULINK® environment. The modelled electric vehicle was simulated, and the total harmonic distortion (THD) was obtained before incorporating a passive electronic filter to lessen the effect of electric vehicle (EV) integration on the distribution network. Similarly, renewable energy sources (solar photovoltaic and wind) were integrated into the electromobility model, and their effects on the THD value were determined. It was discovered that the total harmonic distortion was within the acceptable International Electrotechnical Commission (IEC) standard of 5% when the electromobility source had a passive filter incorporated. It was discovered that the filter reduces the THD value from 195% to 0.03% both in Vehicle-to-Grid and Grid-to-Vehicle modes. Thus, filters should be incorporated into EVs to minimize the effect of their integration into the distribution network. This research work is unique because it combines the effects of electromobility (electric vehicle) load, renewable energy sources and passive filters on harmonics.